Anticancer potential of nitric oxide (NO) in neuroblastoma treatment. Issue 16 (1st March 2021) - Gordon, Jenna L.; Hinsen, Kristin J.; Reynolds, Melissa M.; Smith, Tyler A.; Tucker, Haley O.; Brown, Mark A.
Abstract : S -Nitrosoglutathione (GSNO) reduces cell viability, inhibits cell division, and induces cell cycle arrest and apoptosis in neuroblastoma cells. Abstract : The most common extracranial solid tumor in childhood, paediatric neuroblastoma, is frequently diagnosed at advanced stages and identified as high risk. High risk neuroblastoma is aggressive and unpredictable, resulting in poor prognosis and only ∼40% five-year survival rates. Herein, nitric oxide (NO) delivered via the S -nitrosothiol, S -nitrosoglutathione (GSNO), is explored as an anticancer therapeutic in various neuroblastoma lines. After 24 h of treatment with GSNO, cell viability assays, as assessed by resazurin and MTT ((3-4, 5-dimethylthiazol-2-yl)-2, 5-diphyltetrazolium bromide), consistently identified a moderate, ∼13–29%, decrease in metabolic activity, colony formation assays revealed notably significant reduction of clonogenic activity, and cytotoxicity assays revealed a visibly significant reduction of total number of cells and live cells as well as an increase in number of dead cells in treated cells versus untreated cells. Thrillingly, RNA-sequence analysis provided highly valuable information regarding the differentially expressed genes in treated samples versus control samples as well as insight into the mechanism of action of NO as an anticancer therapeutic. Favorably, the collective results from these analyses exhibited tumoricidal, non-tumour promoting, and discriminatory characteristics, illuminating the feasibility and significance of NO as a cytotoxic adjuvant in neuroblastoma treatment.